Role of ABCC2 common variants in intrahepatic cholestasis of pregnancy - Sookoian, Silvia (The WJG Press and Baishideng, 2008)
The pathogenesis of intrahepatic cholestasis of pregnancy (ICP), a disorder that adversely affects maternal wellbeing and fetal outcome, is unclear. However, multiple factors probably interact along with a genetic predisposition. We would like to add some comments on a paper recently published concerning the role of ABCB11 and ABCC2 polymorphisms in both ICP and contraceptive-induced cholestasis, especially in the light of our recently published findings about a positive association between ICP and ABCC2 common variants.